Factors related to completeness of basic immunization in children during pandemic in Yogyakarta - Masta Hutasoit; Vira Nur Safitri (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: The Government of Indonesia requires basic immunization for infants aged less than 1 year to reduce morbidity, disability, and infant mortality from preventable diseases. Objective: To find out the factors related to the completeness of basic immunization for children during the pandemic in Sleman Yogyakarta. Methods: This study used a cross sectional approach carried out in the work area of ​​the Berbah Public Health Center, Sleman Yogyakarta. The data collection technique in this study used a total sampling technique with the number of respondents as many as 42 mothers who had children aged 9-24 months. Bivariate data analysis using chi square test. Results: It was found that maternal education (P=0.024), family support (P=0.010) had a significant relationship to the completeness of basic immunization in infants. Conclusion: Mother's knowledge and family support are factors that have a strong relationship with the completeness of basic immunization in children.